Англо-русский юридический словарь: Ок. 50 000 терминов / С. Н. Адрианов, А. С. Берсон, А. С. Никифоров - Адрианов Сергей Николаевич (Руссо, 1998)
Экземпляры: ЧЗ (20151126) / Инвентарный номер: 33695 / Цена: 45.00 / Авт.знак: А 81 / ГРНТИ: 10 / ББК: 67я2